2022
DOI: 10.48550/arxiv.2207.11072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clustering and flocking of repulsive chiral active particles with non-reciprocal couplings

Abstract: Recently, non-reciprocal systems have become a focus of growing interest. Examples occur in soft and active matter, but also in engineered quantum materials and neural (brain) networks. Here, we investigate the impact of non-reciprocity on the collective behavior of a system of (dry) chiral active matter. Specifically, we consider a mixture of "circle swimmers" with steric interactions and non-reciprocal alignment couplings. Based on hydrodynamic equations which we derive from a set of Langevin equations, we e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…A question that has attracted a significant interest in the past few years is how MIPS is affected by chirality (i.e., ω = 0). Both studies based on particle-based simulations [29,93] and on the analysis of continuum equations [50,94,95] found that circular swimming (in 2D) tends to hinder MIPS. Remarkably, however, chirality also leads to a new phenomenon which does not occur for ω = 0: the emergence of finite dynamical clusters which counter-rotate with respect to the surrounding gas [29,93].…”
Section: Classmentioning
confidence: 99%
See 1 more Smart Citation
“…A question that has attracted a significant interest in the past few years is how MIPS is affected by chirality (i.e., ω = 0). Both studies based on particle-based simulations [29,93] and on the analysis of continuum equations [50,94,95] found that circular swimming (in 2D) tends to hinder MIPS. Remarkably, however, chirality also leads to a new phenomenon which does not occur for ω = 0: the emergence of finite dynamical clusters which counter-rotate with respect to the surrounding gas [29,93].…”
Section: Classmentioning
confidence: 99%
“…These rollers show various phases such as a disordered gas phase, rotating flocks and also vortices where the particles have aster-like orientations. A very recent work considers CAPs with non-reciprocal interactions, showing how these can qualitatively alter the (linear) stability of the disordered state [50].…”
Section: Classmentioning
confidence: 99%